Tandem in General Election Campaign 2019: A Strategy Supported by Political Parties and Political Patronage - Rahman, Fathur; Sujoko, Anang (Jurnal Politik Indonesia: Indonesian Political Science Review, 2020)
This study examines the Tandem campaign's impact in a general election as a strategy, supported by the party, and political patronage in Indonesia. Tandem is a campaign for more than one candidate. The investigation finds that tandem not only has the parallel model in numbering tandem with candidates from the People‘s Representatives Council (DPR) and the Regional People’s Representatives Council (DPRD), but the zigzag model also applies because of agreement from candidates. This pattern is supported by the political party, so the parliamentary threshold can be achieved, accounting for 4 % in DPR and 15 % in DPRD. During Regional Leaders Election (Pilkada), a political party can promote its candidate for a regional leader without paying another candidate from another party. Tandem can grow political patronage, and the candidates for DPR can be patrons of the DPRD candidates. This is because DPR members have many resources while candidates for DPRD as clients understand no further than the condition in their electoral district and social-political behavior, or they can even serve as broker-vote buyers. We hypothesize that this is a part of finding a solution to political costs in general elections.